Aquaculture farmers’ spatial distribution and intention to adopt the Sistem Pengurusan Kawalan Biosekuriti Perikanan (Biodof-Map) - Lokman, Eleanor Daniella; Man, Norsida; Che’Ya, Nik Norasma (2024)
Aquaculture is crucial to food supply and economic growth supported by Industry Revolution 4.0 to boost output. Malaysian Department of Fisheries (DOF) developed a Web-GIS system, a spatial system focusing on aquaculture. However, farmers are unfamiliar with the system. The Theory of Planned Behaviour (TPB) is employed to examine the attitudes, subjective norms, and perceived behavioural control of Malaysian Aquaculture Farmers (MAFs) throughout Malaysia in relation to BioDOF-Map. Questionnaire was used in the present quantitative research, with 278 respondents. Data was analysed using descriptive, spatial, correlation, and regression analysis techniques. 65.8% of respondents are farm landlords. 29.2% respondents own 3.1 to 4 hectares, and 69.1% reside 2 to 3 km from their farm. Notably, 49.6% own family land and 9.7% grow crops or vegetables off-farm. Cage culture or aquaculture were respondents’ activities. Perak (11.15%), Pahang and Selangor (10.07%) have the most residents. Spatially, aquaculture farming decisions are influenced by housing and town location. With a mean of 4.55 and SD of 0.296, MAFs intend to use BioDOF-Map. Correlation showed a significant association between attitude and intention at 0.01 level of significance (r=0.980, p=.000), supporting the hypothesis. At 0.01 significance level, subjective norms, and intention are linear (r = 0.325, p =.000), fails to reject the null hypothesis. At 0.01 level of significance (r=0.966, p=.000), perceived behavioural control and intention fails to reject the null hypothesis. Regression shows a significant association between attitude and intention (β = 0.635, t = 20.704, p<0.05). Attitude has the highest beta value of 0.635, predictors variable showed a significant and unique variance total R2 97.4% (0.974). This study contributed to the literature on intention to adopt. The model can be utilized to increase farmers’ intention to adopt. Ministry of Agriculture and Food Security (KPKM) and stakeholders should develop policies and programmes to improve subjective norms and behavioural control towards the system.